2018
DOI: 10.1002/jcp.27493
|View full text |Cite
|
Sign up to set email alerts
|

CXCL8 gene silencing promotes neuroglial cells activation while inhibiting neuroinflammation through the PI3K/Akt/NF‐κB‐signaling pathway in mice with ischemic stroke

Abstract: Objective: Ischemic stroke is known as a neurodegenerative disorder, which induces long-period tissue damage. Chemokine (C-X-C motif) ligand 8 (CXCL8) is involved in acute inflammation and tumor progression through the phosphoinositide-3-kinase/ protein kinase B/nuclear factor-κB (PI3K/Akt/NF-κB)-signaling pathway. In this study, we aimed to explore the mechanism of CXCL8 in ischemic stroke in relation to the PI3K/Akt/NF-κB-signaling pathway.Methods: Microarray-based gene expression profiling of peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 47 publications
(72 reference statements)
3
24
0
Order By: Relevance
“…In a mouse IS model, the expression of IL-8 in peripheral mononuclear cells could affect the occurrence of IS by regulating the PI3K/Akt/NF-kb signaling pathway. After reducing the expression of IL-8, it reduced the infarct size, activated the neurogliocytes, and improved neural function recovery (Lv et al, 2019). This study further suggests that IL-8 expression in the brain increases in patients with DM, as do the activities of the NF-κB, MAPK, TNF, and PI3K-Akt signaling pathways.…”
Section: Discussionsupporting
confidence: 52%
“…In a mouse IS model, the expression of IL-8 in peripheral mononuclear cells could affect the occurrence of IS by regulating the PI3K/Akt/NF-kb signaling pathway. After reducing the expression of IL-8, it reduced the infarct size, activated the neurogliocytes, and improved neural function recovery (Lv et al, 2019). This study further suggests that IL-8 expression in the brain increases in patients with DM, as do the activities of the NF-κB, MAPK, TNF, and PI3K-Akt signaling pathways.…”
Section: Discussionsupporting
confidence: 52%
“…Research studies have confirmed that activation of NFthe ‐κB signal pathway widely exists in various kinds of CNS damages, including ischemic stroke, 63 , 64 , 65 ICH, 44 , 45 , 66 and SAH, 36 , 67 and its repression could notably reduce these brain impairments. 36 , 63 , 64 , 65 , 67 In our previous research, we also have verified that NF‐κB signal pathway‐related proteins were significantly upregulated after ICH, and its suppression could markedly alleviate ICH‐induced EBI and neurobehavioral deficiency. 44 , 45 Similarly, our current results suggest that PUE could significantly improve ICH‐induced EBI and related molecular mechanisms possibly by PI3K/Akt signal activation‐mediated suppression of the NF‐κB pathway.…”
Section: Discussionmentioning
confidence: 96%
“…The sections were examined and photographed under fluorescence microscopy (DFC310 FX, Leica, Germany). Apoptosis index (AI) = apoptotic cell number/total cell number × 100% [17].…”
Section: Methodsmentioning
confidence: 99%